Exploring luxury hotel consumption values, attitudes and revisit intention in the post-pandemic era - Ng, Siew Imm; Yao, Yue; Kamal Basha, Norazlyn (University Malaysia Sarawak, 2024)
In the post-pandemic era, luxury hotels face recovery challenges owing to economic recession, heightened safety awareness among consumers, and uncertainty. To address this, we proposed a modified value-attitude-behaviour model based on consumption value and human values theory. Our study sample included 421 Chinese consumers. The findings show that functional, social, epistemic, and security values significantly influence attitudes towards luxury hotels, which, in turn, affect revisit intentions. Attitudes mediate these relationships, with a positive impact on revisit intentions. Emotional value’s influence on attitudes and revisit intentions has decreased post the pandemic, providing practical insights for luxury hotel management. This research provides empirical evidence supporting both theoretical and managerial insights, offering perceptions into the formation of customer attitudes and revisit intentions towards luxury hotels in the post-pandemic era.